The Chain Mediating Effect of Health Literacy and Self-Care Ability on the Relationship Between Dysmenorrhea Symptoms and Negative Emotions Among Chinese Female College Students - Luo Y; Liu D; Sun G; Lu Y; Fang M; Zhang Y; Xu C; Bai G; Chen C (International Journal of Women's Health)
Yixin Luo,1,* Dongrun Liu,1,* Guangfan Sun,2 Yuwen Lu,2 Mei Fang,2 Yang Zhang,2 Caixia Xu,2 Guifang Bai,2 Chaoran Chen1 1Institute of Nursing and Health, School of Nursing and Health, Henan University, Kaifeng, Henan, People’s Republic of China; 2Reproductive Surgery, Zhongshan Boai Hospital, Zhongshan City, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guifang Bai, Reproductive Surgery, Zhongshan Boai Hospital, Zhongshan City, 528405, People’s Republic of China, Email 781154838@qq.com Chaoran Chen, Institute of Nursing and Health, School of Nursing and Health, Henan University, Jinming Avenue, Kaifeng, Henan, 475004, People’s Republic of China, Email kfccr@126.comBackground: Dysmenorrhea, a common concern among female college students, is closely linked to anxiety and depression, particularly during the early menstrual phase (the first one to two days of menstruation), when cramping pain in the lower abdomen and other discomforts occur. This study aims to assess the current status of dysmenorrhea and negative emotions among female college students and explore the factors influencing the relationship between menstrual pain and negative emotions.Methods: A total of 1,117 female college students with moderate to severe dysmenorrhea (based on a Visual Analog Scale (VAS) ≥ 4) were recruited from five universities in Guangdong Province through purposive and convenience sampling to complete an online survey between August and October 2024. Data were collected using multiple standardized scales. Pearson correlation coefficients were used to examine the relationships between variables. Multiple linear regression analysis was conducted to analyze the effects of variables with statistically significant differences (P < 0.05) identified through one-way ANOVA, independent sample t-tests, and correlation analysis on psychological levels. Structural Equation Modeling (SEM) was used to explore mediating effects.Results: This study shows that dysmenorrhea symptoms, health literacy, self-care ability, and negative emotions are significantly correlated. Health literacy and self-care ability play a chain mediating role between dysmenorrhea symptoms and negative emotions, with a mediating effect of 0.026, accounting for 4.87% of the total effect.Conclusion: The findings suggests that health literacy and self-care ability play a chain-mediating role between dysmenorrhea symptoms and negative emotions. It provides new insights for intervening in emotional issues related to dysmenorrhea in female college students. Universities and healthcare institutions should focus on enhancing health literacy and self-care abilities among female college students, offering effective health education and resources to help them better manage menstrual pain and reduce anxiety and depression.Keywords: dysmenorrhea symptoms, health literacy, self-care ability, negative emotions, female college students